New miRNA Signature Heralds Human NK Cell Subsets at Different Maturation Steps: Involvement of miR-146a-5p in the Regulation of KIR Expression - Pesce, Silvia; Squillario, Margherita; Greppi, Marco; Loiacono, Fabrizio; Moretta, Lorenzo; Moretta, Alessandro; Sivori, Simona; Castagnola, Patrizio; Barla, Annalisa; Candiani, Simona; Marcenaro, Emanuela (Frontiers in Immunology, 2018)
Natural killer cells are cytotoxic innate lymphoid cells that play an important role for early host defenses against infectious pathogens and surveillance against tumor. In humans, NK cells may be divided in various subsets on the basis of the relative CD56 expression and of the low-affinity FcγRIIIA CD16. In particular, the two main NK cell subsets are represented by the CD56bright/CD16-/dull and the CD56dull/CD16bright NK cells. Experimental evidences indicate that CD56bright and CD56dull NK cells represent different maturative stages of the NK cell developmental pathway. We identified multiple miRNAs differentially expressed in CD56bright/CD16- and CD56dull/CD16bright NK cells using both univariate and multivariate analyses. Among these, we found a few miRNAs with a consistent differential expression in the two NK cell subsets, and with an intermediate expression in the CD56bright/CD16dull NK cell subset, representing a transitional step of maturation of NK cells. These analyses allowed us to establish the existence of a miRNA signature able to efficiently discriminate the two main NK cell subsets regardless of their surface phenotype. In addition, by analyzing the putative targets of representative miRNAs we show that miR-146a-5p, may be involved in the regulation of killer Ig-like receptor (KIR) expression. These findings contribute to a better understanding of the physiologic significance of miRNAs in the regulation of NK cell development/function. Moreover, our results suggest that miR-146a-5p targeting, resulting in KIR down-regulation, may be exploited to generate/increment the effect of NK KIR-mismatching against HLA-class I+ tumor cells and thus improve the NK-mediated anti-tumor activity.